Utilizing News Text Development in Teaching Reading: A Case at English Course for Public Relation of Universitas Bina Sarana Informatika - Mursyid Kasmir Naserly; Yousef Bani Ahmad (ELT in Focus, 2018)
In this study the researchers sought to develop a pattern of reading teaching in the English for Public Relations course. The development of the pattern researchers realized in the reading exercise pattern using news text media. This certainly will arouse the curiosity of the participants, compared to the pattern of practice materializing formal texts or even reading texts with old themes. The use of news texts that are more casual in nature certainly can be used as a benchmark for students' reading skills, especially in honing the scanning and skimming skills they have learned before. How fast the participants in reading and understanding the meaning they read is the target of success that the researchers saw, so that in the future researchers can find other ways to apply the method of scanning and skimming with other text media.